Faktor Penentu Kualitas Pengungkapan Csr Di Perusahaan-Perusahaan Bursa Efek Indonesia - Griselda Ayu Ratnadewati (LPPM UNIBI, 2020)
Nowadays, Indonesian’s companies put more attention to corporate social responsibility disclosure. The purpose of the study is to determine factors that affect the quality of social responsibility disclosure. This study uses multiple linear regression with SPSS 20 to analyze data. The population of the study is all companies listed on Indonesian Stock Exchange in 2014-2018. Total sample obtained using purposive sampling technique is 80 data samples, consisting of 16 companies for 5 years. This study found that partially industrial type affects the quality of social responsibility disclosure. Meanwhile, board gender diversity and slack resources do not affect the quality of social responsibility disclosure. This study also found that simultaneously, board gender diversity, industrial type, and slack resources affect the quality of social responsibility disclosure.